1996
DOI: 10.2223/jped.604
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of systemic arterial blood pressure during neonatal period in term newborns adequate for gestacional age

Abstract: IntroduçãoA pressão arterial sistêmica (PA) pode ser determinada através de diferentes métodos. As técnicas mais largamente utilizadas incluem registro direto da pressão intraarterial, uso do esfigmomanômetro e palpação, ultra-somdoppler e oscilometria 1 . Os registros diretos são obtidos no RN por meio de cateterização da aorta abdominal, através da artéria umbilical. Constitui a forma mais precisa de medida da PA, mas está associada a complicações como infecção, vasoespasmo e formação de trombos, além de dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…These findings highlight the importance of establishing adequate reference values for BP during this stage of life. 11 Tracking possible BP changes and trajectories over a prolonged period can identify trends in blood pressure behavior 6 and risk factors. 3 Elevated BP levels during childhood can also predict high BP during adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These findings highlight the importance of establishing adequate reference values for BP during this stage of life. 11 Tracking possible BP changes and trajectories over a prolonged period can identify trends in blood pressure behavior 6 and risk factors. 3 Elevated BP levels during childhood can also predict high BP during adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, Matsouka et al . 6 tracked blood pressure levels during the neonatal period and found increased blood pressure levels during the first month of life. However, the blood pressure levels found in the present study were lower than those in the Brazilian study by Vilarim and Alves, 9 which identified normative blood pressure levels for Brazilian newborns.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations